Clustering Penilaian Kinerja Guru Menggunakan Algoritma K-Means - Donni Tambunan; M. Hasyim Arrasyid; Eferoni Ndruru (TIN: Terapan Informatika Nusantara, 2022)
Assessment of teacher quality is one of the important things that schools really need. Imelda Medan Private High School every year conducts a performance appraisal of teachers. However, there are still obstacles such as printing and distributing questionnaires which are considered less efficient, requiring a lot of money and effort. As well as not using a particular system or method in processing the results of the questionnaire into grades and graphs for monthly reports and determining the best teacher. The clustering technique is one technique for assessing a teacher's performance and the K-Means algorithm is one of the clustering technique algorithms. This technique is very suitable for use in this study, namely evaluating the performance of teachers at Imelda Medan Private High School. The result of this study is the application of data mining with the K-Means algorithm method which can assess a teacher's performance using the criteria that have been obtained at the data collection stage.